Penatalaksanaan Fraktur Mahkota Kompleks dengan Pulpektomi Vital pada Gigi Desidui: Laporan Kasus - Suci N. Rahmadani; Putri K. W. Mahendra (Universitas Sam Ratulangi, 2024)
Abstract: Traumatic injury in teeth and their supporting tissues is often found in children including pre-school children (2- 4 years old) with the highest prevalence is crown fractures of anterior teeth. Management of crown fracture in primary teeth needs to be performed properly for the teeth to last until their exfoliations. We reported a four years old girl came to RSGM Prof. Soedomo and the chief complain was fractures of primary maxillary teeth. The patient complained of pain and easy bleeding of the teeth. Intraoral examination showed crown fractures with exposed pulp of teeth 51 and 61, vital, and negative percussion, palpation and mobility tests. Radiographic examination did not reveal any fracture of the alveolar bone, and good permanent tooth buds. The patient was uncooperative. The diagnosis of this case was complex crown fractures of teeth 51 and 61. The treatment was vital pulpectomy on teeth 51 and 61 using GIC as the final restoration. The vital pulpectomy was performed in two visits with a non-pharmacologic body restrain behavior management. In conclusion, the management of complex crown fracture with vital pulpectomy shows good result. Collaboration among dentist, parents, and patient greatly influences the success of treatment, especially in case of crown fracture et cause traumatic injury. Keywords: complex crown fracture; primary tooth; vital pulpectomy Abstrak: Cidera traumatik pada gigi dan jaringan pendukungnya banyak dijumpai pada anak di antaranya anak pra sekolah (usia 2-4 tahun) dengan prevalensi terbanyak ialah fraktur mahkota gigi anterior. Penatalaksaan fraktur mahkota gigi desidui harus dilakukan dengan tepat agar gigi dapat bertahan hingga waktunya lepas. Kami melaporkan kasus seorang anak perempuan berusia 4 tahun datang ke RSGM Prof. Soedomo dengan keluhan gigi desidui rahang atas patah. Pasien mengeluhkan adanya rasa sakit dan mudah berdarah pada gigi tersebut. Pemeriksaan intraoral menunjukkan fraktur mahkota dengan pulpa terbuka gigi 51 dan 61; vital tidak terdapat kegoyahan, serta tes perkusi dan palpasi negatif. Pemeriksaan radiografi tidak didapatkan adanya fraktur pada tulang alveolar dan benih gigi permanen baik. Anak tidak kooperatif. Diagnosis untuk kasus ini ialah fraktur mahkota kompleks gigi 51 dan 61. Perawatan yang dilakukan berupa pulpektomi vital pada gigi 51 dan 61 dengan GIC sebagai restorasi akhir. Pulpektomi vital dilakukan dalam dua kali kunjungan dengan pendekatan manajemen perilaku non farmakologis body restrain. Simpulan kasus ini ialah penatalaksanaan fraktur mahkota kompleks dengan pulpektomi vital memberikan hasil yang baik. Kerjasama antara dokter gigi, orang tua dan pasien, sangat memengaruhi keberhasilan perawatan khususnya pada kasus fraktur mahkota akibat cidera traumatik. Kata kunci: fraktur mahkota kompleks; gigi desidui; pulpektomi vital